Improvement of antibiotic production by increased oxygen solubility through the addition of perfluorodecalin - Elibol, M (Wiley, 2001)
A perfluorocarbon (PFC), namely perfluorodecalin, was added to fermentation medium to increase the medium's oxygen solubility. The antibiotic concentration obtained in the absence of PFC was 45mgdm(-3), whereas it was 90mgdm(-3) in the presence of 10% (v/v) PFC. On the other hand, biomass concentration decreased from 5.7kgm(-3) to 2.9kgm(-3) by adding 10% PFC. The use of PFC in the fermentation medium also reduced the formation of mycelial pellets. The values of the mass transfer coefficient, k(L)a, measured in the medium with PFC were found to be in the range of 122-175h(-1) during the active growth phase which were two to three times higher than those in the medium containing no PFC. Furthermore, the maximum oxygen uptake rates obtained at the stationary phase with and without PFC were 7mmol dm(-3)h(-1) and 4.9mmol dm(-3)h, respectively. The actual effect of PFC on actinorhodin fermentation was demonstrated by applying different operational strategies to the system. (C) 2001 Society of Chemical Industry.
Keywords: antibiotic; actinorhodin; S coelicolor; perfluorocarbon; oxygen solubility